On the average spectral efficiency of interference-limited full-duplex networks - Alves, Hirley; De Lima, Carlos H. M. [UNESP]; Nardelli, Pedro H. J.; Demo Souza, Richard; Latva-Aho, Matti (European Alliance for Innovation n.o., 2014)
This paper studies how dense deployments of small cells with full duplex technology perform under various network configurations and channel conditions. The resulting interference at the receiver of interest combines both its intrinsic self-interference and components from co-channel base stations and user equipment transmissions. Network deployment is represented by a Poisson field of transmitters, while a composite channel with log-normal shadowing and Nakagami-m fading describes our propagation model. Herein, a stochastic geometry framework is used to first characterize the interference profiles for the full duplex scenarios under consideration, and then derive closed-form expressions for the Average Spectral Efficiency (ASE). Results show that the Self-Interference (SI) dominates the aggregate interference component and Full-Duplex (FD) networks outperform Half-Duplex (HD) networks in terms of ASE for SI cancellation values lower than -70dB. © 2014 ICST.